2021
DOI: 10.31014/aior.1993.04.02.298
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Elementary Teaching Undergraduate Program in Terms of 21st Century Skills

Abstract: 21st century skills emerge is one of the most crucial competencies that need to be considered in teacher education. With this in mind, the fundamental objectives of this study is to analyze the pre-service teachers’ competencies and perceptions of 21st century skills that are effectively present in today’s world. Explanatory mixed method was applied in this study. The aim of the study is to reveal the adequacy of the undergraduate elementary teaching program in the acquisition of 21st century skills from the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The post-test score was higher than the pre-test results; therefore, Flipgrid positively impacts student learning outcomes. It follows the twenty-first-century theory where technology can help students understand the material, solve problems, and equip students to keep up with the changing skills needed (Kanmaz, 2021). Thus, the data collection results on learning English in junior high school showed that the role of technology is crucial in the learning process, encouraging students to increase their knowledge and abilities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The post-test score was higher than the pre-test results; therefore, Flipgrid positively impacts student learning outcomes. It follows the twenty-first-century theory where technology can help students understand the material, solve problems, and equip students to keep up with the changing skills needed (Kanmaz, 2021). Thus, the data collection results on learning English in junior high school showed that the role of technology is crucial in the learning process, encouraging students to increase their knowledge and abilities.…”
Section: Discussionmentioning
confidence: 98%
“…Integration technology and English learning allow practical language learning. Students get complete access and interact with their friends and teachers quickly and interactively (Kanmaz, 2021). Also, they have more time to explore their English skills.…”
Section: Introductionmentioning
confidence: 99%